Characterization of Potential Polysaccharide Utilization Systems in the Marine Bacteroidetes Gramella Flava JLT2011 Using a Multi-Omics Approach - Tang, Kai; Lin, Yingfan; Han, Yu; Jiao, Nianzhi (Frontiers in Microbiology, 2017)
Members of phylum Bacteroidetes are distributed across diverse marine niches and Flavobacteria is often the predominant bacterial class decomposing algae-derived polysaccharides. Here, we report the complete genome of Gramella flava JLT2011 (Flavobacteria) isolated from surface water of the southeastern Pacific. A remarkable genomic feature is that the number of glycoside hydrolase (GH) genes in the genome of G. flava JLT2011 is more than two-fold higher than that of other Gramella species. The functional profiles of the GHs suggest extensive variation in Gramella species. Growth experiments revealed that G. flava JLT2011 has the ability to utilize a wide range of polysaccharides for growth such as xylan and homogalacturonan in pectin. Nearly half of all GH genes were located on the multi-gene polysaccharide utilization loci (PUL) or PUL-like systems in G. flava JLT2011. This species was also found to harbor the two xylan PULs and a pectin PUL, respectively. Gene expression data indicated that more GHs and sugar-specific outer-membrane susC-susD systems were found in the presence of xylan than in the presence of pectin, suggesting a different strategy for heteropolymeric xylan and homoglacturonan utilization. Multi-omics data (transcriptomics, proteomics, and metabolomics) indicated that xylan PULs and pectin PUL are respectively involved in the catabolism of their corresponding polysaccharides. This work presents a comparison of polysaccharide decomposition within a genus and expands current knowledge on the diversity and function of PULs in marine Bacteroidetes, thereby deepening our understanding of their ecological role in polysaccharide remineralization in the marine system.